The evidence base for psychotropic drugs approved by the European Medicines Agency: a meta-assessment of all European Public Assessment Reports. (27th April 2020) - Erhel, Florian; Scanff, Alexandre; Naudet, Florian
Abstract: Aims: To systematically assess the level of evidence for psychotropic drugs approved by the European Medicines Agency (EMA). Methods: Cross-sectional analysis of all European Public Assessment Reports (EPARs) and meta-analyses of the many studies reported in these EPARs. Eligible EPARs were identified from the EMA's website and individual study reports were requested from the Agency when necessary. All marketing authorisation applications (defined by the drug, the route of administration and given indications) for psychotropic medications for adults (including drugs used in psychiatry and addictology) were considered. EPARs solely based on bioequivalence studies were excluded. Our primary outcome measure was the presence of robust evidence of comparative effectiveness, defined as at least two 'positive' superiority studies against an active comparator. Various other features of the approvals were assessed, such as evidence of non-inferiority v . active comparator and superiority v . placebo. For studies with available data, effect sizes were computed and pooled using a random effect meta-analysis for each dose of each drug in each indication. Results: Twenty-seven marketing authorisations were identified. For one, comparative effectiveness was explicitly considered as not needed in the EPAR. Of those remaining, 21/26 (81%) did not provide any evidence of superiority against an active comparator, 2/26 (8%) were based on at least two trials showing superiority against active comparator and three (11%) were based on one positive trial; 1/26 provided evidence for two positive non-inferiority analyses v . active comparator and seven (26%) provided evidence for one. In total, 20/27 (74%) evaluations reported evidence of superiority v . placebo with two or more trials. Among the meta-analyses of initiation studies against active comparator (57 available comparisons), the median effect size was 0.051 (range −0.503; 0.318). Twenty approved evaluations (74%) reported evidence of superiority v . placebo on the basis of two or more initiation trials and seven based on a single trial. Among meta-analyses of initiation studies against placebo (125 available comparisons), the median effect size was −0.283 (range −0.820; 0.091). Importantly, among the 89 study reports requested on the EMA website, only 19 were made available 1 year after our requests. Conclusions: The evidence for psychiatric drug approved by the EMA was in general poor. Small to modest effects v . placebo were considered sufficient in indications where an earlier drug exists. Data retrieval was incomplete after 1 year despite EMA's commitment to transparency. Improvements are needed.